Perceived accreditation benefits, participation and organizational commitment in hospital accreditation performance - Jivita Catleya Basarah; Andry Andry; Anastina Tahjoo (Intelektual Pustaka Media Utama, 2022)
Good perceptions on accreditation have an important role to play in achieving five-star accreditation and continuous implementation of accreditation. In the pre-survey, we found that the problem, a low perceived accreditation benefits, participation, and organizational commitment, as well as employees’ performance of the accreditation process that did not meet the target. The purpose of this study was to analyze the impact of the perceived benefits of accreditation on the performance of employees in the accreditation process. The research method used was a causal analysis study with a cross-sectional quantitative approach and a path analysis hypothesis test. The sample was taken by means of an objective sampling of X mother & children hospital (Rumah Sakit Ibu dan Anak/RSIA) health personnel. The results found that the perception of the benefits of accreditation had a positive and significant effect through mediation of participation and commitment to performance. The impact of the perceived benefits of accreditation, participation and organizational commitment on employee performance is 46.9%. This research implies for hospital management to optimize the performance of the accreditation process by increasing the perception of the benefits of accreditation through training, sharing, assessment, award and monitoring and evaluation involving all employees.